Pengaruh Sosial Ekonomi Lebak Lebung pada Masyarakat Desa Tanjung Serang Kecamatan Kayuagung Kabupaten Ogan Komering Ilir 2010-2022 - Mei, Mei; Wargadalem, Farida R. (Riwayat: Educational Journal of History and Humanities, 2025)
This study discusses the social and economic impacts of the lebak lebung system on the community of Tanjung Serang Village, Kayuagung District, Ogan Komering Ilir Regency during the period 20102022. The lebak lebung system, which is inherited from generation to generation, is a form of traditional auction-based water management that grants management rights to the auction winner (pengemin). The type of research is qualitative with in-depth interview methods, observation, and documentation studies. And the method used is the historical method with a heuristic approach, source criticism, interpretation, and historiography. The results of the study indicate that the existence of lebak lebung has had a positive impact on increasing community income, opening up employment opportunities, strengthening social interaction, and increasing food security and local economic empowerment. In addition, the integration of local wisdom with regional regulations has encouraged more sustainable and accountable management. In conclusion, the lebak lebung system not only contributes to economic welfare, but also becomes part of the social and cultural identity of the local community.